GAMBARAN BODY IMAGE PADA REMAJA USIA 16 – 18 TAHUN - Nia Agustiningsih (Jurnal Kesehatan Mesencephalon, 2019)
Adolescence is a period where physical, emotional and cognitive development or thinking occurs. Adolescents will evaluate the changes or physical development based on their thinking. The purpose of this study is to describe the body image of adolescents aged 16-18 years. This research is a descriptive research. The population in this study were all adolescents aged 16-18 years in Kromengan Vocational School with a simple random sampling technique with a sample of 149 people. The results showed that respondents who had a very good body image amounted to 5 people (3.35%), who had good body image there were 74 people (49.66%), who had enough body image 68 people (45.64% ) and there are 2 people who have body image (1.35%). Based on these results, the majority of adolescents are able to adapt to physical changes and have positive acceptance so that information and education are needed that can maintain positive perceptions of adolescents and improve adolescent perceptions that are still lacking in self-acceptance seen by body image Keyword: Body image, adolescence